India’s first percutaneous tricuspid valve implantation: Valve-in-valve is a treatment option for bioprosthetic valve dysfunction - A.B. Gopalamurugan; R. Mohamed Abubacker; Prashant Vaijyanath (IHJ Cardiovascular Case Reports, 2017)
Bioprosthetic valve dysfunction leading to haemodynamically significant consequences is well recognised. Traditional treatment of choice has been conventional re-do surgical valve replacement. However, over the last decade, percutaneous solutions such as Valve-in-valve (VIV) implantations has emerged as a well-established option for such patients Dvir et al. (2014), V. Bapat et al. (2012) and Piazza et al. (2011). We report India’s first tricuspid valve-in-valve implantation with a balloon expandable valve through a trans-jugular approach to treat dysfunctional tricuspid valve dysfunction.